The variation of the Solanaceae family trichomes found in the Cendana Hill, Sedan District, Rembang Regency - Yusuf, Moh Ilham; Mustofa, Ali; Imas Cintamulya (Inornatus: Biology Education Journal, 2025)
This study aimed to identify the variation of trichomes in the Solanaceae family found in the Cendana Hill of Sedan District, Rembang Regency. This study used the trichome printing method and the results were observed under a microscope. This study found trichomes glandular and non-glandular from the six Solanaceae species with various types. Different variations were found from the six species of the Solanaceae family, i.e: stellata, acicular, uncinate, hydathode, simplex and curved. The variations of trichomes from the Solanaceae family have different characteristics and shapes. This study identified six species from the Solanaceae family that have variations in the shape and type of trichomes on the epidermal layer of leaves, i.e: Solanum melongena var. melongena, var. serpentinum, Solanum lycopersicum, Solanum nigrum, Physalis angulata, Nicotiana tabacum, and Capsicum frutescens. Non-glandular trichomes act as a mechanical defense against pathogens and herbivores, while glandular trichomes have the function of secreting secondary metabolites, such as alkaloids and flavonoids, which play a role in chemical defense.